Análisis del control interno del área de inventario en la Empresa Districamp S.A dedicada a la fabricación y distribución de insumos acuícolas - Bazurto Martínez, Britney Anahis (2024)
The research project titled "Analysis of the inventories of the company Districamp S.A." Examine problems related to the company's inventories, using information from financial reports from national and international sources of recognized prestige. The study aims to identify, determine and compare relevant aspects for the importation of jute bags, considering organizational interests. To achieve these objectives, a mixed methodology is used that combines qualitative and quantitative analysis of information, which allows numerical analysis, interpretations, characterizations and decision-making based on the results obtained. The conclusions and recommendations presented in the study are based on the analyzed reports, responding to each of the stated objectives. In short, it demonstrates the great importance of jute bags for the company, underlining their strategic value in importing and marketing, and consolidating them as a current policy and business model.